When did Lithuania Lose its Energy Independence? Primary Energy Consumption in Lithuania in 1927–1960 from the Viewpoint of the Economic History of Energy - Norkus, Zenonas; Ambrulevičiūtė, Aelita (Lietuvos istorijos studijos, 2025)
In the summer of 2024, the Seimas of the Republic of Lithuania approved the National Energy Independence Strategy which sets full energy independence as the long-term goal for Lithuania’s energy development. This should be achieved in around 2050, when Lithuania is expected to become a net energy exporter. At the same time, Lithuania will have completed the second major energy transition: replacing fossil hydrocarbon energy sources with renewable energy sources. By using the methodology of the economic history of energy (Astrid Kander, Paolo Malanima, Paul Warde et al.), we answer the question of identifying when Lithuania lost its energy independence (i.e., we ask: when did the share of imported primary energy sources in their total consumption started exceeding the share of local sources)? We have also estimated when the first major energy transition in Lithuania reached a turning point (i.e., when the share of fossil hydrocarbon fuels in the total consumption of primary energy sources started exceeding the share of renewable energy sources).